Noon Mountain (Jub. 4:25) = Moriah Mountain (Aethiopica, 2003)
Miscellaneous Article ATTENTION: Due to copy-right no online publication is provided.
Keywords: Book of Jubilees; Moriah Mountain; Ge'ez; Hebrew; Linguistics